Kaartdijin Bidi (Learning Journey): Place-based Cultural Regeneration at University - Sandra Wooltorton; Lauren Stephenson; Kathie Ardzejewska; Len Collard (Australian Journal of Environmental Education)
Imagine being in a university that functions in a place-based culturally regenerative way. In this concept paper, the authors bring together theory, practice, and experience, in the service of transforming universities towards place-based cultural regeneration. At present, Australian universities operate using an economic philosophy of neoliberal corporatism characterised by hierarchical management strategies, competitive tendencies, patriarchal values, and discourse characterised by bifurcation or binary thinking. These features illustrate a worldview that is entangled with the meta crises of our times such as climate change, species loss, hatred/intolerance, and unfathomable violence. The authors consider ways of moving towards a place-based, Indigenous-informed, practical, relational way of learning, being and knowing differently. The paper tentatively assembles a local, place-based culturally regenerative worldview based on living, vibrant, responsive places that embrace people who collaborate with Country – in the Indigenous sense of deep relationality. Within this worldview, the authors propose collaborative ways of governing, teaching, learning, and leading that is necessary for place-based cultural regeneration. In conclusion, the authors outline a pathway towards universities as places of regenerative cultures, which prioritise the nurturing of learning to live and work beyond the current societal paralysis on the road to collapse.